​​Influence of coir and flax fiber lengths on fracture toughness of fly ash, slag, and silica fume-based geopolymer concrete - Saavedra-Flores, E (Nature Research, 2026)
Geopolymer concrete (GC), which is produced from industrial by-products rich in aluminosilicates such as fly ash, ground granulated blast furnace slag, and silica fume, serves as an environmentally sustainable substitute for conventional Portland cement-based concrete. Fracture toughness is vital for GC, as its brittle matrix is prone to crack initiation and propagation, affecting structural safety. Enhancing fracture resistance ensures reliable performance under various loading modes. Coir and flax fibers were chosen for their availability, sustainability, and ability to bridge cracks and improve post-crack energy absorption, providing insights for optimizing natural fiber reinforcement. Researchers have turned to natural fibers such as coir and flax to overcome the limited ductility and mechanical shortcomings typical of geopolymer composites. These fibers were specifically chosen for their potential to enhance both toughness and post-cracking energy absorption in the matrix. This investigation focused on how different aspect ratios of coir and flax fibers affected the fracture properties of GC when exposed to various loading modes: Mode I, Mode III, and their combination. To ensure a controlled comparison, GC specimens were cast with fiber lengths set at 20 mm, 40 mm, and 60 mm, while maintaining a fixed fiber volume fraction of 0.5%. Additionally, the microstructure of the geopolymer composite was characterized using scanning electron microscopy, X-ray Diffraction, thermogravimetric analysis, and fourier transform infrared spectroscopy analyses. The results demonstrated that the incorporation of 40 mm coir and flax fibres enhanced the fracture toughness of the GC by up to 20.65% under mixed-mode loading (loading angle = 20°), 18.96% under Mode I, and 9.70% under Mode III. In contrast, extending the fibre length to 60 mm led to a deterioration in performance, with FRTS values falling by as much as 2.64% below those of the control composite, a decline attributable to fibre agglomeration and the consequent disruption of effective stress transfer. Microstructural analyses reveal that a dense, continuous sodium aluminosilicate hydrate gel network augmented by residual crystalline phases such as quartz and mullite substantially reinforces the geopolymer matrix. Coir fibres exhibit superior interfacial bonding and more stable debonding characteristics than flax fibres, thereby promoting more effective crack bridging and yielding greater fracture toughness. Complementary thermal and chemical characterisation further indicates enhanced matrix stability, reduced porosity, and improved load-transfer efficiency, with partial carbonation imparting additional microstructural densification. © The Author(s) 2026.